Modern Azerbaijani language: social integration and interlanguage relations - Almammadova, Sabina (INOITs ALMAVEST Ltd., 2022)
The linguistic situation in the modern Republic of Azerbaijan is considered, namely, the special role of borrowed terms in enriching the vocabulary of the modern Azerbaijani language, mediated by the interrelationships of languages in the globalized linguistic and cultural space.
Keywords: historical; language; science; development